Pengaruh Inovasi Produk dan Price Discount Terhadap Kepuasan Konsumen Starbucks Coffe (Studi Kasus Starbucks Coffee Green Pramuka) - Ramlan Samuel; Tinton Ramadhan (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of product innovation and price discount on customer satisfaction and product innovation and price discount simultaneously affect customer satisfaction. In this study the method used is a quantitative method and the unit of analysis used is linear regression analysis using Nonprobabilty Sampling sampling techniques with a sample size of 175 respondents by distributing questionnaires distributed via Google Form. Hypothesis test results (t test) showed that product innovation and price discounts significantly influence consumer satisfaction, indicated by t arithmetic of 6.864 and 5.247, which is greater than t table 1.973. In addition, the results of this study with the F test, showed that simultaneously product innovation variables and price discounts affect customer satisfaction.